Design of air filter box and duct bellow for range extender engine in medium/heavy duty applications - Andersson, Louise; Hermansson, Linus (My University, 2023)
This study focuses on designing an air filter box for REX (range extender) engine applications in medium/heavy duty trucks. The aim is to meet the technical re quirements set by Aurobay and design an air filter box and duct bellow that fulfill the necessary criteria. The research questions addressed include identifying current designs and filters used in the automotive industry and establishing technical re quirements. Along with exploring design possibilities, and evaluating how the new designs can meet and exceed expectations. By comparing existing designs, establish ing requirements, and exploring design possibilities, this study provides a design for an air filter box and duct bellow that meet the requirements and can be produced. It also provides Aurobay with a foundation for future air filter box designs. The study includes a literature review and benchmarking of existing air filter system designs in the automotive industry. Technical requirements are established through interviews, considering factors such as airflow, air quality, pressure drop, leakage, durability, and space constraints. CAD (Computer Aided Design) modeling and CFD (Computational Fluid Dynamics) simulations are conducted to evaluate the design parameters’ impact. The results highlight the significance of inlet placement, inlet angle, guides, distance between the inner wall and filter, filter thickness, radius on the outlet, and inlet design on the air filter box’s performance. Two significant findings emerge from the study. The radius on the inlet and outlet are important factors that affects the UI (uniformity index) over the outlet and the air filter. Additionally, placing the bellows on the duct at a greater distance from the box improves uniformity over the MAF (mass flow sensor). The recommended final concept is a rectangular air filter box with a flat-shaped filter. It incorporates a short duct bellow for cost benefits and the inlet is positioned near the top of the engine to create a shorter path for a dirty side duct. The air filter box is divided into two parts for optimal placement and replacement of the air filter and is securely fastened using screws. Hexagonal pattern ribs on the top lid and outer surface of the bottom part enhance structural integrity, while rounded corners and edges prioritize safety. The recommended concept fulfills the requirements and serves as a guide for Aurobay’s future air filter box designs.
Keywords: Air filter box, air filter, duct bellow, limited space, CAD, CFD, REX